(untitled) (Pain medicine, 2019)
Neuroblastoma is a malignant tumor that develops from the stem cells of the sympathetic ganglia and the adrenal medulla and belongs to the group of neuroendocrine tumors. It is most often localized in the adrenal glands and the retroperitoneal space, less – in sympathetic ganglia of the neck and thoracic cavity. Pain syn-drome is one of the leading manifestations in patients with disease progression. Unlike other patients, a pain syndrome in oncological patients is not a temporary or periodic sensation, it has no physio-logical expediency, it does not have a protective mechanism, but, on the contrary, pain in this group of patients leads to inadaptation, distorted perception of pain and small impulses, most importantly, accompanied by various disorders of the functions of the central nervous system in the patient’s body.